2022
DOI: 10.31897/pmi.2022.2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the geomechanical state of the rock mass when mining salt deposits with stowing

Abstract: The technogenic impact of mining on the environment is analyzed and the transition to geotechnology with stowing to reduce the impact of mining operations is proposed. The results of the research work devoted to the justification of parameters of the development of salt deposits with stowing and the definition of the influence of stowing on the dynamics of deformation of the underworked rock massif are presented. The relevance of research aimed at creating a safe and efficient technology for the transition fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…This technology is most often used in the development of water-soluble ores with low value. Extraction of water-soluble ores is characterized not only by high losses (up to 65%) [ 7 ] of minerals left in pillars, but also by the formation of a large amount of waste generated during the extraction and processing of water-soluble ores. The volume of the generated waste is 60–70% of the total volume of the extracted ore mass [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is most often used in the development of water-soluble ores with low value. Extraction of water-soluble ores is characterized not only by high losses (up to 65%) [ 7 ] of minerals left in pillars, but also by the formation of a large amount of waste generated during the extraction and processing of water-soluble ores. The volume of the generated waste is 60–70% of the total volume of the extracted ore mass [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plasticity of natural salt pillars causes deformation changes in them, which leads to their destruction [ 7 ]. Destruction of pillars causes deformation disturbances of the overlying rock mass [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the application process of gangue fluidization backfilling technology in a goaf, the study of residual space size, shape, and slurry diffusion law of the caving goaf is an essential point for the smooth implementation of gangue fluidization backfilling technology and guarantees the filling effect. Given such problems, some scholars at home and abroad have done much research on the subsidence law of overlying strata in stopes [16]; the fracture morphology of overlying strata in caving goaves [17,18]; and the law of crushing, swelling, and compaction of fractured rock mass by using similar material simulation and numerical simulation methods [19,20]. For example, Qian et al [21] showed that the overburden fracture in the caving goaf would form an "O" ring pattern.…”
Section: Introductionmentioning
confidence: 99%
“…These mining impacts pose significant environmental, socio-economic and mining layout challenges. For this reason, these adverse impacts and mitigation measures have been extensively studied in several countries, including Russia [6], Australia [7,8], the United Kingdom [9], South Africa [10,11], India [12,13] and Germany [14]. Meanwhile, the number of large coal power plants, characterized by pithead plants, is increasing rapidly in major coal mining countries around the world.…”
Section: Introductionmentioning
confidence: 99%